Diagnostic Ability of Chest Ultrasound in Selective Paediatric Pneumonia Alternative to CT scan: A single-center Comparative Observational Study - Thareeb, Marwa Kareem; Alghani Zghair, Muna Abid; Hassan, Qays Ahmed (Journal of Nepal Paediatric Society, 2022)
Introduction: Chest CT is the gold standard method of the diagnostic evaluation of patients with pneumonia. Lung sonography has been lately explored as an alternative modality to decrease radiation hazards. This study aimed to evaluate the diagnostic ability of lung ultrasonography in detecting paediatric pneumonia at presentation and follow up and comparing findings with chest CT scan. Methods: A cross-sectional observational study was performed at a paediatric hospital from August 2019 to April 2021. We studied 106 children (ages from 45 days to 14 years) referred by the paediatrician with clinical data of pneumonia. All children underwent CT chest examination; 90 showed positive, while 16 showed no pneumonia. Ultrasonography was performed on all patients within 24 hours after CT examination. Results: We found that lung ultrasound showed 100% specificity, 82.2%, sensitivity in the diagnosis of paediatric pneumonia, accuracy was 84.9%, positive predictive value was 100% and negative predictive value was 50%. Their sensitivity and specificity are 100% in complicated pneumonia by parapneumonic effusion, empyema, and abscess formation. Conclusions: Chest ultrasound is a simple technique that can be performed in everyday practice, with high specificity and sensitivity compared to a chest CT scan in diagnosis and follow up of pneumonia in the pediatric age group.